THE INTRODUCTION OF RESOURCE-SAVING TECHNOLOGIES FOR THE SEPARATION OF FREIGHT AND PASSENGER TRAFFIC - Kurgan, M. B.; Khmelevska, N. P.; Cherniakov, M. M. (Science and Transport Progress, 2010)
The analytical dependences of electric energy losses on average track section gradient values, train mass and freight traffic density are determined.